2020
DOI: 10.1155/2020/1584541
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Amniotic Membrane Stem Cell (AMSC) Metabolite Product and Vitamin E for Wrinkles, Spots, and Pores in Photoaging

Abstract: Background. It is expected that a combination of amniotic membrane stem cell metabolite product (AMSC-MP) and vitamin E after fractional CO2 laser as laser-assisted drug delivery (LADD) will provide better effects in photoaging treatment as the combination reaches the target. This promises an option for photoaging therapy in the future. Materials and Methods. Sixty women with photoaged skins were involved in this experimental study. They were then divided into two groups. The treatment group received a topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…1 Skin aging in women can affect mood, self-confidence and quality of life. 3 In addition, skin aging in women is associated with decreased dehydroepiandrosterone (DHEA) hormone. It causes the reduction of type I procollagen expression, which then decreases collagen synthesis and accelerates collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Skin aging in women can affect mood, self-confidence and quality of life. 3 In addition, skin aging in women is associated with decreased dehydroepiandrosterone (DHEA) hormone. It causes the reduction of type I procollagen expression, which then decreases collagen synthesis and accelerates collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesian people are prone to photoaging, as Indonesia is a tropical country with constant sun exposure throughout the year. 3 In Indonesia, chemical peeling has been used as a treatment option for photoaging patients. Glycolic acid peeling was performed on 72 photoaging patients, representing 15.8% of all photoaging patients (455 patients) at Medical Cosmetics Division Dermatology and Venereology Department of Dr. Soetomo General Academic Hospital Surabaya between 2011 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Their anti-aging potential has been associated with the release of growth factors, angio-modulatory cytokines, anti-bacterial peptides, and anti-inflammatory molecules [ 82 ]. A study showed that a topical application of AMSC metabolic products combined with vitamin E significantly improved wrinkles, ultraviolet spots, and pores in patients with photoaging [ 83 ]. ADSCs have also shown promise for facial skin rejuvenation [ 84 ].…”
Section: Reviewmentioning
confidence: 99%
“…Statically, there is a significant difference (p 0.05) shown in Table 3. In the moisture test for each volunteer gave good results, especially for formula (3), which consists of aloe vera essence of 5 % combined with vitamin E. Due to the increase in hydration of the skin from the coverage of the biocellulose sheet mask and the combined effect of aloe and vitamin E that improves skin elasticity and also provides collagen, preventing wrinkles from taking place [28].…”
Section: Good Antioxidant Testing Greatly Affects the Effect Of Antio...mentioning
confidence: 99%